Material properties of clay and lime plaster for structural fire design. (18th December 2019) - Johanna, Liblik; Judith, Küppers; Alar, Just; Birgit, Maaten; Siim, Pajusaar
Summary: Clay and lime plaster are traditional surface finish materials used on historic timber walls and ceilings. Today, hardly any fire technical properties or design parameters exist that consider such plasters as fire protection materials for timber structures. This hinders the fire assessment of existing building structures and disadvantages their use in modern design solutions where healthy and sustainable materials are increasingly favoured. This research follows the safety philosophy of EN 1995‐1‐2 to describe the fire protection ability of plasters. This paper investigates the temperature‐dependent thermal properties of historic plasters by presenting series of material‐specific tests and furnace tests carried out under standard fire exposure conditions. Experimental studies are supported by numerical heat transfer simulations. Results demonstrate particularities between the fire protection ability of clay and lime plaster, however, highlight the need for further investigations in terms of their thermophysical performance and standardisation at the European level. Design parameters are presented and discussed in future perspective. This work demonstrates a basic research to plan and design full‐scale fire tests according to EN 13381‐7:2019.